Stigma Revisited : Implications of the Mark - Hannem, Stacey, 1979-; Bruckert, Chris, 1960- (Book collections on Project MUSE., 2012)
A return on Erving Goffman's seminal 1963 Stigma: Notes on the Management of Spoiled Identity.